On Sublimation. (4th August 2016) - Civitarese, Giuseppe
Translations of summary: Although it encapsulates the Freudian theory of art, the theory of sublimation has become outmoded. What is more, since its inception there has always been something ill‐defined about it. Does it use sexualized or de‐sexualized drive energy? Is it a defence or an alternative to defence? Does it serve Eros or Thanatos? Is it useful in clinical work or is it unusable? The only, albeit uncertain, aid to a definition relies on the extrinsic criterion of concrete artistic realization. My aim here to revisit and possibly 'reinvent' sublimation in the light of certain principles of the pre‐Romantic aesthetics of the sublime. Both are theories of spiritual elevation, in other words, elevation that moves towards abstract thinking, and of man's 'moral' achievement; and both attempt to explain the mystery of aesthetic experience. On the one hand, the aesthetics of the sublime offers a modern myth that helps us articulate a series of factors occasionally referred to by various authors as constitutive of sublimation but which have not been incorporated into a single organic framework: loss and early mourning work; the earlier existence of a catastrophic factor – to be regarded, depending on the situation, as either traumatic or simply 'negative'; the correspondence with a process of somatopsychic categorization which coincides with subjectivity. On the other hand, it also helps us grasp the experience of negative pleasure empathically, living it 'from the inside'.